Probiotics and Synbiotics for Glycaemic Control and Beta-Cell Function in Children with Type 1 Diabetes Mellitus: A Meta-Analysis of Randomised Controlled Trials - Michael Theodore; Salim Aljufri; Noviane Angrella (HM Publisher, 2026)
Gut dysbiosis has been implicated in the pathogenesis and progression of type 1 diabetes mellitus (T1DM), and microbiota-based interventions have been proposed as adjuncts to insulin. The paediatric evidence remains fragmented and the effect on residual beta-cell function has not been a focus. This meta-analysis quantified the effect of probiotic and synbiotic supplementation on glycated haemoglobin (HbA1c) and synthesised beta-cell and immune outcomes in children with T1DM. PubMed/MEDLINE was searched for randomised controlled trials (RCTs) of oral probiotics, prebiotics, or synbiotics added to insulin in T1DM, with HbA1c as the primary outcome. Standardised mean differences (SMD, Hedges’ g) were pooled with a random-effects model (DerSimonian–Laird). Subgroup, leave-one-out, an a-priori paediatric-only sensitivity, and exploratory small-study analyses were performed. Risk of bias used Cochrane RoB 2.0. Beta-cell and immune outcomes were synthesised narratively. Seven RCTs (453 participants) were included. Supplementation produced a significant, small-to-moderate reduction in HbA1c (pooled g = −0.50, 95% CI −0.71 to −0.30; z = −4.94, p < 0.0001), with low heterogeneity (I² = 11.0%, τ² = 0.008, Q = 6.74, df = 6, p = 0.345) and a prediction interval of −0.84 to −0.17, corresponding to about 0.3 to 0.5 HbA1c percentage points. The effect was consistent across disease stage (between-group p = 0.957), was preserved in the strictly paediatric analysis (g = −0.54), and was robust to leave-one-out removal. Beta-cell outcomes were inconsistent. Supplementation was safe. In conclusion, in children with T1DM, probiotics and synbiotics conferred a modest but consistent improvement in HbA1c, without convincing evidence of beta-cell preservation. The intervention appears safe but the clinical magnitude is small and does not currently justify a change to routine practice.